Harmonisasi Hukum dan Kebhinekaan: Analisis Perkawinan Beda Agama (Studi Putusan MK 24/PUU-XX/2022, SEMA 2/2023, dan MA 1400K/PDT/1986) - fitri indah nursanti (CV Rewang Rencang, 2025)
This article examines the legal challenges of interfaith marriage in Indonesia through a juridical and philosophical approach, focusing on the disharmony between positive law, constitutional principles of religious freedom and the right to form a family, and the value of pluralism. Article 2 paragraph (1) of Law No. 1 of 1974, which requires that marriage validity be based on each party’s religious law, often becomes a legal barrier for interfaith couples. Through an analysis of the Ramos Petege case, Constitutional Court rulings, and Supreme Court Circular No. 2 of 2023, this article reveals the absence of a clear legal mechanism for recognizing the legality of interfaith marriage. The study applies legal theories from prominent legal philosophers, including Hugo Grotius’ natural law, Lon L. Fuller’s morality of law, and the principle of Bhinneka Tunggal Ika, to examine the gap between positive law and substantive justice. The findings indicate that Indonesia’s legal system remains influenced by religious interpretations, lacks inclusivity, and fails to ensure equal protection of individual rights in a multicultural society. Therefore, legal reform through more progressive legislation and judicial interpretation is necessary.